Call to improve transparency of trials of non-regulated interventions. (27th March 2015) - Dal-Ré, Rafael; Bracken, Michael B; Ioannidis, John P A
Abstract : The public and clinicians require transparent, quality evidence for all interventions. Trials of non-regulated interventions are common, and efforts to improve their registration and publication compared with drug trials are overdue, say Rafael Dal-Ré, Michael Bracken, and John Ioannidis